PERANCANGAN KAPAL PENANGKAP IKAN (GILLNET) 170 GT UNTUK DAERAH OPERASI SELAT MENTAWAI DENGAN KECEPATAN 10 KNOT - Irfan Pujianto, (2020)
West Sumatra is one of the provinces in Indonesia with huge fishing potential. Unfortunately, this potential has not been explored to the maximum. Of the potential of around 565 thousand tons a year, only around 200 thousand can be achieved in 2016. In 2017, it is not much different, which is only about 212 thousand tons that can be achieved. Therefore, it is necessary to increase the number of fishing vessel in West Sumatra. With the increase in the number of fishing vessel in the region, it is expected to be able maximize the potential of capture fisheries that in previous year could not be maximized. For this reason, the authors designed a fishing vessel with 170 GT tonnage that was planned to use a fishing gear in the form of a surface drift gillnet and would operate to catch fish in the Mentawai Strait waters with a port base at the Bungus Ocean Fishing Port. This ship is designed using the comparison and literacy methods. The result of the design obtained fishing vessels with total lenght (Loa) = 26 m, perpendicular lenght (Lpp) = 24.3 m, Breadth (B) = 7.6 m, Depth (H) = 3.8 m, Draft (T) = 3.2 m, block coefficient (Cb) = 0.5275, displacement = 319.532 ton, engine power 479 Hp with a maximum speed of 10 knots, and can accomodate 85 tons of fish. Besides this design ship also has stability that has met the requirements of the IMO (International Maritime Organization).